Exosome CTLA-4 Regulates PTEN/CD44 Signal Pathway in Spleen Deficiency Internal Environment to Promote Invasion and Metastasis of Hepatocellular Carcinoma - Wang, Yongdan; Li, Pan; Mao, Shuai; Mo, Zhuomao; Cao, Zhirui; Luo, Jin; Zhou, Meiling; Liu, Xifeng; Zhang, Shijun; Yu, Ling (Frontiers in Pharmacology, 2021)
Hepatocellular carcinoma (HCC) is one of the most common primary cancers, and its pathogenesis is complicated and difficult to screen. Currently, there is no effective treatment. In traditional Chinese medicine, a large proportion of patients with HCC have been diagnosed with spleen deficiency syndrome and treated with tonifying traditional Chinese medicine, which has significant clinical efficacy. However, the role and molecular mechanism of spleen deficiency in HCC remain unclear. In this study, 40 mice were randomly divided into four groups: control, spleen deficiency (SD), HCC, and SD-HCC groups. The liver cancer model of spleen deficiency was established by reserpine induction and orthotopic transplantation. The effects of spleen deficiency on the proliferation, apoptosis, invasion, and metastasis of HCC cells were studied by cell proliferation, cell apoptosis, cell scratch, and transwell assay. We found that compared with the HCC group, the protein expressions of cytotoxic T lymphocyte antigen 4 (CTLA-4), programmed cell death protein 1 (PD-1), phosphatase and tensin homolog (PTEN), and AKT (also known as protein kinase B or PKB) in the exosomes of the SD-HCC group were up-regulated. In addition, the metastases and self-renewal of exosomes in the SD-HCC group were more aggressive than those in the HCC group, which could be partially reversed with the addition of CTLA-4 inhibitors. Further studies showed that in the internal environment of spleen deficiency, CTLA-4 promoted tumor invasion and metastasis by regulating the PTEN/CD44 pathway. In conclusion, our findings suggest that spleen deficiency internal environment exosomes CTLA-4 regulate PTEN/CD44 signal pathway to promote the proliferation, self-renewal, and metastasis of liver cancer.